2006
DOI: 10.1364/ao.45.007661
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a thick polyvinyl alcohol-acrylamide photopolymer for data storage using a combination of angular and peristrophic holographic multiplexing

Abstract: The capability of polyvinyl alcohol-acrylamide photopolymer materials to obtain angularly multiplexed holographic gratings has been demonstrated [Appl. Phys. B 76, 851 (2003)]. A combination of two multiplexing methods-peristrophic and angular multiplexing-is used to record 60 holograms. An exposure schedule method is used to optimize the capability of the photopolymerizable holographic material and obtain holograms with a higher, more uniform diffraction efficiency. In addition, because of this exposure sched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 20 publications
1
38
0
Order By: Relevance
“…The density of the layers was calculated using the mass of the deposited amount of solution and the thickness of the layer. It has been found that the density of TEA-sample and NPG-sample is approximately 1.03 g/cm 3 and 2.61 g/cm 3 , respectively. Thus, the photopolymer layer containing NPG is the denser and less porous material than the photopolymer layer containing TEA.…”
Section: Dependence Of Diffraction Efficiency On Relative Humidity Lementioning
confidence: 99%
See 1 more Smart Citation
“…The density of the layers was calculated using the mass of the deposited amount of solution and the thickness of the layer. It has been found that the density of TEA-sample and NPG-sample is approximately 1.03 g/cm 3 and 2.61 g/cm 3 , respectively. Thus, the photopolymer layer containing NPG is the denser and less porous material than the photopolymer layer containing TEA.…”
Section: Dependence Of Diffraction Efficiency On Relative Humidity Lementioning
confidence: 99%
“…Photopolymer materials can be used in holographic data storage [1][2][3][4][5][6][7], diffractive and refractive optical elements [8,9], solar concentrators [10,11], holographic interferometry [12][13][14][15][16] and holographic sensors [17][18][19]. Acrylamide-based photopolymers are widely covered in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of multiplexing schemes to store many holograms in the same volume such as angular [12][13][14][15], peristrophic [16,17], shift multiplexing [18,19] or by more than one of these techniques in combination [20][21][22], which are used to store multiple holograms at the same location. In these methods, angular multiplexing is probably the most common in which the reference beam is incident upon the sample at difference angle to record each hologram.…”
Section: Introductionmentioning
confidence: 99%
“…In this technique, after a hologram is recorded, the recording material is rotated around a certain rotational axis so as to record another hologram [13][14][15]. This type of multiplexing has the added advantage that it can be combined with other multiplexing methods to increase the storage density of holographic storage systems [16]. In the present work, an exposure-scheduling method was used to exploit the entire dynamic range [17] of the material and to record equal strength holographic gratings in it.…”
Section: Introductionmentioning
confidence: 99%